Uji Analisis Tegangan Motor 3 Phase Dengan Sistem IoT (Elconika: Jurnal Teknik Elektro, 2022)
IoT (Internet of Things) is a concept related to sensors and software to communicate, control, connect, exchange through other devices using the internet. IoT is also related to smart devices because these devices can help complete human work. The application of IoT is widely used to monitor voltage and current on motor performance anywhere and anytime. The purpose of this research is to analyze the voltage of a 3 phase motor with an IoT (Internet of Things) system. This research uses an experimental study method starting from software design, namely the Blynk application along with Arduino programming, which later the results of the coding program are transferred to the ESP32 module to run the ZMPT101B voltage sensor. as a voltage meter. Then design the physical form of the research tool in the form of designing contactors, Thermal Overload, MCB, indicator lights, On Off switch buttons, and assembling a power circuit and control circuit with neatly arranged wiring to run Motor I and Motor II which will later be measured manually. with AVOmeter and with ZMPT101B voltage sensor with IoT system. From the experimental results of the tool testing, the average value of the AVOmeter measuring instrument I VR 233.1 VS 234 VT 232.5 and motor II VR 233.1 VS 233.6 VT 233 then for the sensor measuring instrument ZMPT101B motor I VR 230, 8 VS 231.4 VT 230.7 and motor II VR 228.2 VS 228.7 VT 230.2 while the average error voltage of motor I was 0.8% while motor II was 1.7%.